Active sway control of a gantry crane system using LQR controller - Khairul Azmi, Mohd Yusoff (2010)
This project is about the development of Active Sway Control of a Two-Dimensional Gantry Crane (2D – Gantry Crane) System using Linear Quadratic Regulator (LQR) controller. This project analyzes on how to reduce the sway angle of the rode when it is released from certain position. This system is a 2D system because the rode’s movement is only along the x and y axes. The 2D Gantry Crane system consists of several elements such as the cart, rode, actuator, payload and controller. The movement of the cart will cause the swaying motion of the rode because the speed of the cart is directly proportional with the sway angle of the rode. If the speed of the cart is increased, the sway angle also increases. The swaying motion will decrease the efficiency of the crane system. In order to increase the efficiency of the crane system, the crane will need an efficient controller to reduce the sway angle. The rode of the gantry crane will be controlled by using LQR controller. LQR is derived by a set of linear differential equation and the cost is described by a quadratic functional. The main objective of LQR controller is to obtain the best performance of dynamic system at the minimum cost. Performance of the system focuses on the sway angle caused by the rode’s movement and the Power Spectral Density (PSD) of the sway angle response